MICROBIAL SCREENING ON RAW AND DRY SELECTED MARINE SPECIES FROM NAGAPATTINAM DISTRICT, TAMIL NADU, INDIA - DR.B.DHANALAKSHMI; DR.G.CHITRA (International Journal of Pharma and Bio Sciences, 2015)
The present study was conducted for microbiological assessment of six selected marine species from Nagapattinam district. Total viable colony count, E.coli, Vibrio species, Salmonella species, total yeast count and total mould count were determined in Stolephorus commorsonnii, Hilsa ilisha, Otolithes ruber, Sardinella longiceps, Ilisha elongata and Penaeus indicus. The total viable colony count of the raw fishes and prawn varied from 0.10- 8.30% and the dry fishes and prawn varied from 0.10-1.20%. The E.coli of the raw fishes and prawn varied from 0.20-0.80% and the dry fishes and prawn varied from 0.08 to 0.20%. The vibrio species of raw fishes and prawn varied from 1-4% and the dry fishes and prawn varied from 0.2 – 0.20%.In the present study salmonella, yeast and mold were not detected in both fresh and dried samples. The total viable colony count, E.coli and vibrio species were reduced in the dry fishes while E.coli was completely absent in Stolephorus commersonnii, Sardinella longiceps and Ilisha elongata.